Effectiveness of DKI Governor Regulation No. 31 of 2019 on Rivers in the Capital Region of Jakarta - Rifdhan Ismeth Nyandra (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
This journal aims to analyze the effectiveness of DKI Governor Regulation No. 31 of 2019 concerning Development and Revitalization of Water Resources Infrastructure in an Integrated with the Naturalization Concept of Rivers in the Jakarta Area. This journal analyzes the concept of water naturalization as a solution to restore river water quality in Jakarta. In addition, this journal also analyzes how this Pergub can overcome problems related to the restoration of river water quality in Jakarta. The results of this journal show that this Pergub is effective in improving the quality of river water in Jakarta by applying the concept of water naturalization.